2017
DOI: 10.1038/srep40350
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal analysis of malaria incidence in the Peruvian Amazon Region between 2002 and 2013

Abstract: Malaria remains a major public health problem in the Peruvian Amazon where the persistence of high-risk transmission areas (hotspots) challenges the current malaria control strategies. This study aimed at identifying significant space-time clusters of malaria incidence in Loreto region 2002–2013 and to determine significant changes across years in relation to the control measures applied. Poisson regression and purely temporal, spatial, and space-time analyses were conducted. Three significantly different peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…Both hotspots have been a long-standing regional source of P. vivax and P. falciparum transmission, as earlier studies suggested [7,13,19]. Our results support previous findings from Venezuela, Brazil and Peru showing that P. vivax malaria spatial heterogeneity is characterized by localities of high risk interspersed with others of moderate or low risk [11,30,31,32]. Due to their stability or persistence over time, the hotspots detected here could be predictive of prospective malaria incidence in the surrounding areas as has been found in other studies [33,34,35].…”
Section: Discussionsupporting
confidence: 92%
“…Both hotspots have been a long-standing regional source of P. vivax and P. falciparum transmission, as earlier studies suggested [7,13,19]. Our results support previous findings from Venezuela, Brazil and Peru showing that P. vivax malaria spatial heterogeneity is characterized by localities of high risk interspersed with others of moderate or low risk [11,30,31,32]. Due to their stability or persistence over time, the hotspots detected here could be predictive of prospective malaria incidence in the surrounding areas as has been found in other studies [33,34,35].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, despite decreased HBR levels leading to a much lower estimated EIR in CAH in October 2012 (period of baseline survey), the entomological study found a high infection rate of collected mosquitoes (1.47%) which indicated onward malaria transmission in the area [ 28 ], and the potential new increase of cases if ecological conditions were favourable. This is exactly what happened in November–December 2012 [ 13 ] following the early onset of heavy rains generating an abrupt height increase of level rivers since October 2012, and consequently damaging and flooding to villages located along the Amazonas River and its tributaries [ 9 ].…”
Section: Discussionmentioning
confidence: 53%
“…Malaria remains an important public health problem in Peru, especially in the Amazonian department of Loreto where most malaria occurs [ 1 – 4 ]. Following the resurgence of malaria in the 1990s [ 5 8 ], which reached an historic peak of 158,115 cases in 1997 [ 9 ], the Loreto Regional Directorate of Health (LRDH) and national Peruvian Ministry of Health (MoH) organized control efforts that were intensified with the support of international agencies, particularly the Global Fund for AIDS, Tuberculosis and Malaria (GFATM) and the US Agency for International Development (USAID) [ 10 ]. Comprehensive community-based interventions were initiated and intensified that included: delivery of long-lasting insecticidal mosquito nets (LLINs) [ 11 ], environmental management with community participation, training of community health workers and microscopists [ 12 ], and “test and treat” interventions incorporating artemisinin-based combination therapy (ACT) for Plasmodium falciparum .…”
Section: Introductionmentioning
confidence: 99%
“…Transmission may have been worsened due to the historic Loreto flood of 2011-2012 that inundated and damaged many riverine communities [62]. During the period between 2002 and 2013, 79% of cases were P. vivax and 21% P. falciparum [11]. A worrisome trend has been the recent increase in the proportion of P. falciparum in 2016 (27%) and 2017 (24%) ( Table 1).…”
Section: Perumentioning
confidence: 99%
“…The malaria landscape in Latin America consists of low transmission interspersed with diverse hot-spots where transmission is spatially and temporally focused [4,[9][10][11]. At a regional scale, reported malaria cases where the Annual Parasite Index (API) is >100 are concentrated in the municipalities of Bolívar, Delta Amacuro, and Sucre (Venezuela); Acre, Amapá, and Amazonas (Brazil); Amazonas, Antioquia, Chocó, and Vichada (Colombia); and Loreto (Peru) [1].…”
Section: Introductionmentioning
confidence: 99%